An integrated biofeedback and psychological skills training program for Canada's Olympic short-track speedskating team - Beauchamp, M. K.; Harvey, R. H.; Beauchamp, P. H. (Journal of Clinical Sport Psychology, 2012)
The present article outlines the development and implementation of a multifaceted psychological skills training program for the Canadian National Short Track Speedskating team over a 3-year period leading up to theVancouver 2010 Olympic Games. A program approach was used emphasizing a seven-phase model in an effort to enhance sport performance (Thomas, 1990) in which psychological skills training was integrated with biofeedback training to optimize self-regulation for performance on demand and under pressure. The biofeedback training protocols were adapted from general guidelines described by Wilson, Peper, and Moss (2006) who built on the work of DeMichelis (2007) and the "Mind Room" program approach for enhancing athletic performance. The goal of the program was to prepare the athletes for their best performance under the pressure of the Olympic Games. While causation cannot be implied due to the lack of a control group, the team demonstrated success on both team and individual levels.